The effectiveness of project-based learning models in teaching short story writing - Martha, Nia Ulfa; Wijayawati, Dyah; Pri Andini, Novita (Universitas Ahmad Dahlan, 2024)
Short story writing instruction in the Indonesian Language Education Study Program at the Faculty of Humanities, Unsoed, aims to help students develop ideas through writing and improve vocabulary mastery. However, students often struggle to generate ideas independently and frequently rely on content from other sources. Additionally, many students have limited vocabulary, which affects their confidence in their writing. The project-based learning model has proven effective when applied to various learning activities. Therefore, this study seeks to examine the effectiveness of project-based learning in short story writing instruction within the Indonesian Language Education Study Program at the Faculty of Humanities, Unsoed. The study employs a quasi-experimental one-group pre-test post-test design, with third-semester students from the program as the population. The third-semester students involved in the study totaled 24. Measurements were taken with a pre-test conducted before the intervention and a post-test after the intervention. The results showed an average pre-test score of 68.25 for short story writing. The average post-test score, after applying the project-based learning model, was 80.33. This represents an increase of 12.08 points following the use of the project-based learning model for short story writing. The use of this model was effective, as the average score improved after the intervention.